Arab modernity and its position on the Sunnah: Research extracted from a master’s thesis) entitled (Historical reading of the Prophet’s Sunnah from the perspective of Muhammad Shahrour and its impact on Kurdistan society) Evaluative Analytical Study - Simo, Yousif; Ibrahim , Ayad (Humanities Journal of University of Zakho, 2022)
A lot of phases and trends emerged in the name of Islam, and their opinions differed on different topics, one of the phases is the modernist thought, which first appeared in France in pursuit of the downfall of the church, and everything related to religion and the call to Islam, making man the standard for everything and prioritizing religious beliefs. Then modernity appeared in the Arab world, they followed the West in terms of dealing with religious texts. This research sheds light on Arab modernist thoughts, in terms of its origin and characteristics, its position on the Prophetic Sunnah, and its materials in that. Through its critical review of the old version of dealing with the Prophetic Sunnah, and also the positive and negative impact of this trend on Islamic reality are focused on in this research.